MEMBANGUN KEMANDIRIAN ANAK: INTEGRASI KEGIATAN AGAMA DAN SOSIAL DI PONDOK PESANTREN AINUL YAKIN - Bono Setyo; Choirun Nijma (Jurnal Studi Pesantren, 2025)
This research aims to understand the dynamics of integrating religious and social activities for children with special needs (ABK) at Pesantren Ainul Yakin Gunung Kidul. Using a qualitative approach with a case study method, this research explores how the pesantren integrates ABK in religious activities such as congregational prayers, Quran memorisation, and religious studies, as well as social activities such as group work and community service. Data was collected through participatory observation, in-depth interviews, and document analysis. The results of the study show that the integration of religious and social activities has a significant positive impact on the psychological, social, and spiritual development of ABK. Religious activities help strengthen ABK's faith and piety, provide inner peace, and reduce stress. Meanwhile, social activities enhance ABK's social skills, self-confidence, and independence, and reduce stigma and discrimination. This research also identifies the challenges faced in integrating ABK, such as physical and cognitive limitations, social stigma, and limited resources. Solutions implemented by the pesantren include providing special assistance, adjusting teaching methods, and educational programs to improve understanding and acceptance of ABK. The integration of religious and social activities at Pesantren Ainul Yakin Gunung Kidul has successfully created an inclusive and supportive environment for ABK to develop holistically. The findings of this research contribute to the development of inclusive education in pesantren and can serve as a model of best practice for other educational institutions.